Pengembangan Desa Wisata Berbasis Pemberdayaan Masyarakat Desa Wisata Kaki Langit Padukuhan Mangunan - Anggit Kurnia Prihasta; Suswanta Suswanta (JURNAL MASTER PARIWISATA, 2020)
Local tourism is currently developed such as Tourism Village development. Kaki Langit Tourism Village one of the tourism village that is currently developing and as a tourism village of Bantul Regency and special region of Yogyakarta. Kaki Langit Tourism Village uses the concept of community empowerment around Padukuhan Mangunan in which the tourism village stands. The natural beauty, cultural diversity, traditions and potential of the community have been the drive of the thriving Kaki Langit Tourism Village. Kaki Langit Tourism Village is developing. The community develops traditional culinary tourism, the lodging of Javanese rural concept, outbound tourism, and nature tourism. With the community being included directly today the community feels the impact of the economy with the additional income they can. This research uses qualitative descriptive methods. The result is that local tourism through the development of tourism village with Community Empowerment is able to bring economic impact to the community. Keywords: Development of tourist village, community empowerment, and economic impact